Upgrading and repairing PCs - Mueller, Scott (Que, 2005)
Appropriate for courses in hardware, PC troubleshooting and repair. Upgrading & Repairing PC's, 13th Academic Edition is a comprehensive reference guide that addresses and resolves hardware problems. This book teaches students about what goes on inside the computer. It also covers PC building, upgrading, repairing and troubleshooting. Written by Scott Mueller, the most trusted, authoritative hardware voice in the industry, it is the complete solution for hardware information.